CT/MRI SEVERITY SCORING IN RHINO-ORBITO-CEREBRAL MUCORMYCOSIS: CORRELATION WITH SURGICAL EXTENT AND 30-DAY OUTCOMES - Hayat, Aanab; Ahmad, Abbas; Khan, Saira; Ahmad, Samira; Liaqat, Salma (Infectious Diseases Journal of Pakistan, 2022)
Background: Rhino-orbito-cerebral mucormycosis (ROCM) is a highly virulent angio-invasive infection with rapid compartmental spread, often requiring escalation of surgery and carrying substantial early mortality. This study aimed to determine the relationship between a CT/MRI severity score, surgical extent, and 30-day outcomes. Material and Methods: Consecutive ROCM patients with baseline CT and/or MRI, operative notes, and 30-day follow-up data were eligible at a tertiary-care centre from March to August 2022. Predefined domains (sinonasal, orbital, cavernous sinus, intracranial/CNS, vascular, and bone) were scored independently by two radiologists to generate a composite severity score. Surgical extent was categorized from endoscopic debridement to combined craniofacial/neurosurgical procedures. Results: Among 62 patients, the severity score increased progressively with surgical extent (Spearman rho = 0.68, p < 0.001). Thirty-day mortality was 22.6% and rose with increasing severity (0% in mild disease; 50% in severe disease). Severity score independently predicted 30-day mortality (adjusted OR per point 1.54) and showed good discrimination (AUC 0.84). Inter-rater reliability for the total score was high (ICC 0.91). Conclusion: CT/MRI severity scoring is a reliable measure that aligns with operative extent and early outcomes and may support standardized reporting and early risk stratification in ROCM. Keywords: Rhino-orbito-cerebral mucormycosis, Computed tomography, Magnetic resonance imaging, Severity scoring, Surgical extent, Prognosis, 30-day outcomes